Surgical and conservative methods for restoring impaired motor function - facial nerve, spinal accessory nerve, hypoglossal nerve (not including vagal nerve or swallowing) - Laskawi, R. (German Medical Science, 2005)
The present review gives a survey of rehabilitative measures for disorders of the motor function of the mimetic muscles (facial nerve), and muscles innervated by the spinal accessory and hypoglossal nerves. The dysfunction can present either as paralysis or hyperkinesis (hyperkinesia). Conservative and surgical treatment options aimed at restoring normal motor function and correcting the movement disorders are described. Static reanimation techniques are not dealt with. The final section describes the use of botulinum toxin in the therapy of dysphagia.